Developing an Islamic digital literacy framework for Muslim youth: A Nominal Group Technique Approach - Mustapha, Ramlan; Jaafar , Abu Bakar; Mahmud, Maziah; Wan Ahmad, Wan Azmi; Malkan, Siti Norma Aisyah; Zakaria, Jazimin; Mohamed, Asjad (Journal of Islamic, Social, Economics and Development, 2025)
This study develops an Islamic Digital Literacy Framework specifically designed for Muslim youth using the Nominal Group Technique (NGT) approach. The research engaged seven subject-matter experts in Islamic studies and education to evaluate and validate the framework components through online NGT sessions. The framework comprises five essential components: Technical Competency, Islamic Knowledge Authentication, Digital Ethics & Adab, Content Creation & Da'wah, and Critical Thinking. The NGT evaluation revealed high expert consensus across all components, with Digital Ethics & Adab, Content Creation & Da'wah, and Critical Thinking achieving perfect scores (100%), while Technical Competency (95.24%) and Islamic Knowledge Authentication (90.48%) also received strong validation. The findings demonstrate the framework's comprehensive integration of technical proficiency with Islamic principles, providing a structured approach for developing digital literacy skills among Muslim youth while maintaining religious values. This research contributes to the field of Islamic digital education by offering a validated framework that addresses the unique challenges faced by Muslim youth in the digital age, ensuring both technical competency and spiritual authenticity in their digital engagement.